Pengaruh Alat Peraga Blok Dienes terhadap Hasil Belajar Matematika pada Siswa Kelas II SD Negeri 8 Singkawang - Ari Septiansyah; Buyung Buyung; Evinna Cinda Hendriana (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aims to: (1) determine the increase in student learning outcomes between the experimental class and the control class (2) see the differences in student learning outcomes after the Dienes Block teaching aid was applied to class II students at SD Negeri 8 Singkawang; (3) determine the effect of dienes block teaching aids on students' KKM mathematics learning outcomes in class II of SD Negeri 8 Singkawang. This type of research is quantitative with a quasi-experimental type with a Non Equivalent Control Group Design research design. The population in this study were all class II students at SD Negeri 8 Singkawang, totaling 59 people. Sampling in research used total sampling techniques. Data collection techniques used learning outcomes test techniques. The data analysis technique used is the Mann Whitney test and effect size. The research results show that: (1) There is an increase in student learning outcomes between the experimental class and the control class. This is shown by the results of the pretest and posttest scores for the experimental class which have increased with an index of 0.442 and are in the medium category. (2) There are differences in student mathematics learning outcomes between classes that use dienes block teaching aids and classes that do not use teaching aids for students. This is shown by the results of the Mann Whitney test, which is 67,000, with a significance value of 0.000 (p < 0.05); (3) There is an influence on students' mathematics learning outcomes. This is shown by the calculation of the effect size test results of 2.186<0.05.